DESCRIBING THE BEHAVIOR OF MANAGER IN BUDGETARY SLACK AND PRODUCTION (CASE STUDY AT BUDGETING IN A STATE-OWNED ENTERPRISE) - Ghazi, Achmad Fariz; Ludigdo, Unti; Prihatiningtias, Yeney Widya (Jurnal Aplikasi Manajemen, 2020)
The objective of this research is to obtain an in-depth insight into budgetary slack practices performed by managers during the budgeting processes of a state-owned enterprise. This research uses qualitative research methods with an interpretive paradigm using a case study approach. The data is collected through interviews, supported by observation and documentation, with informants involved in the planning and budgeting process. The results of this research indicate that the participatory approach adopted in the budgeting process is the trigger of budgetary slack practice. The practice created in the budgeting of sales and production is aimed at achieving maximum profit at the end of the budget period. Asymmetric information and goal clarity are aspects of human behavior that appear in budgetary slack practice. Besides, the applied participation mechanism tends to show symptoms of pseudo participation. Social facts show that budgetary slack practice is created by aspects of human behavior that are motivated by material or financial aspects.